Game of Thrones : A Storm of Swords - Book 3 (2 cases, Part 1 & 2) - Martin, George R. R.; Dotrice, Roy 1925- (New York Random House Audio, 2012)
The three surviving contenders for the throne of the Seven Kingdoms continue to struggle among themselves, Robb defends his kingdom from the Greyjoys, Jon confronts an escalating threat, and Daenerys and her dragon allies continue to grow in power.
Unabridged.
Originally released as sound cassettes in 2004.
Compact discs.
Read by Roy Dotrice.
Keywords: Imaginary wars and battles -- Fiction; Supernatural -- Fiction; Magic -- Fiction; Fantasy fiction; Audiobooks